African studies quarterly (University of Florida, Center for African Studies, 1997)
Presents "African Studies Quarterly," an electronic journal published quarterly by the Center for African Studies at the University of Florida in Gainesville. Posts contact information for the editorial office via street address, telephone number, and e-mail. Lists advisory board and staff members. Offers access to the current issue, as well as to previous issues. Contains articles and related book reviews. Provides information on submissions and links to "African Anthropology."